On solvability of singular periodic boundary-value problems - Staněk, S. (Нелінійні коливання, 2001)
We present conditions ensuring the existence of a solution in the class C¹ ([0, T]) for the singular periodic boundary-value problem (r(x' ))' = H(p(t) + q(x))k(x')f(t, x, x'(0) = x(T),
x'(0) = x'(T).